1968
DOI: 10.1029/wr004i004p00769
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐Water Flow Related to Streamflow and Water Quality

Abstract: A ground‐water flow system in southwestern Minnesota illustrates water movement between geologic units and between the land surface and the subsurface. The flow patterns indicate numerous zones of ground‐water recharge and discharge controlled by topography, varying thicknesses of geologic units, variation in permeabilities, and the configuration of the basement rock surface. Variations in streamflow along a reach of the Yellow Medicine River agree with the subsurface flow system. Increases and decreases in ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…To develop a general concept of ground-water flow in the Missouri Coteau region near the study site, data from the Stutsman County (Huxel and Petri, 1963) and Kidder County (Randich and others, 1962) ground-water studies were used to construct a hydrologic profile through the part of the Coteau shown in figures 3 and 4. Similar types of regional analyses have been done by Meyboom (1963), Maclay andothers (1972), andVan Voast andNovitzki (1968).…”
Section: Regional Ground-water Flowmentioning
confidence: 57%
“…To develop a general concept of ground-water flow in the Missouri Coteau region near the study site, data from the Stutsman County (Huxel and Petri, 1963) and Kidder County (Randich and others, 1962) ground-water studies were used to construct a hydrologic profile through the part of the Coteau shown in figures 3 and 4. Similar types of regional analyses have been done by Meyboom (1963), Maclay andothers (1972), andVan Voast andNovitzki (1968).…”
Section: Regional Ground-water Flowmentioning
confidence: 57%
“…Indicator species analysis for elevation, geology, hydrology, and specific conductance. (Van Voast and Novitzki 1968). Differences in hydroperiod between permanent and ephemeral ponds also influenced species composition, as has been documented in other wetland systems such as semi-permanent prairie wetlands (Poiani and Johnson 1989).…”
Section: ]mentioning
confidence: 82%